Ritual Nyengkolan’t Suku Kerabat di Sekadau Kalimantan Barat - Hendrikus Mangku; Adil Bertus; Florentina Neneng Sabela; Trifonia Ayu (Hunatech Vol. XXX, No. XXX, 2022)
This article is a new study carried out regarding the nyengkolan’t ritual practiced among the Kerabat tribe in Sekadau, West Kalimantan. It is a linguistic anthropology research using the qualitative method. The aim of this study is to document the oral tradition in nyengkolan’t ritual among the Kerabat tribe and analyse the use of language in the ritual. The study has documented the procedures, prohibitions and mantras in the nyengkolan’t ritual. From the discussion, it is found that the use of language in the nyengkolan’t rites also include several Malay words such as ‘enam’, ‘kaki’, ‘sial’, ‘sungai’ and many more. The materials used are mostly the same as those used in the rituals of other tribes in Sekadau.